Development of a Pocket Book Learning Media integrated with Wordwall to Improve Student Learning Outcomes in Natural and Social Sciences Learning - Triana Solikhah; Moh. Farizqo Irvan (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to develop pocket book learning media assisted by Wordwall to improve learning outcomes in natural and social science learning on harmony in ecosystems for grade V students of SDN 2 Sukosono, Jepara Regency. This development is motivated by the limitations of conventional learning media that are less interesting and less effective, as well as the complexity of natural and social science materials that require innovative and interactive media so that students more easily understand the material and are interested in learning. The type of research used is Research and Development (R&D) with the ADDIE development model. Data collection techniques used were interviews, questionnaires, documentation, observation, and multiplechoice tests. This study used data analysis of normality test, sampled paired T-test and N-Gain test. Based on validation from media experts of 93.6% (very feasible), material experts of 90.5% (very feasible), and the results of teacher and student responses of 100% (very feasible), it shows that the pocket book media assisted by wordwall is feasible to use. This can be seen from the results of the paired sample t-test which shows a significance value of 0.000 which means that the average post-test value increases from the previous pre-test average. The N-Gain test shows a value of 0.4 which is said to be effective in the moderate category. Based on the validity, practicality, and effectiveness tests, the Wordwall-assisted pocket book media proved effective in supporting learning. This media is expected to optimally help students' understanding of Harmony in Ecosystems material and improve learning outcomes.